The Master Programe on Intercultural Mediation and Social Intervention - Vieira, Ricardo (2016)
Portugal, in particular, and Europe in general are paradigms of diversity in unity and of the need for intercultural mediation and social intervention policies enabling the reception, hospitality, respect for others and their training in a more inclusive society. From a research and sociological and anthropological level of knowledge, the ESECS-IPLeiria invested, in 2013, on a Master program in Intercultural Mediation and Social Intervention that is a unique example in Portugal. In this paper, in addition to present the Master’s curriculum, we invest in the distinction between preventive mediation, transformative and social empowerment, rather than focusing on solving, typical of conflict resolution, based on the questionable pillar of neutrality and impartiality.